1990
DOI: 10.1111/j.1440-1754.1990.tb02399.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizures associated with 1% cyclopentolate eyedrops

Abstract: A 4.5 year old boy with cerebral palsy presented with seizures associated with facial flushing and tachycardia following the instillation of 1% cyclopentolate, a commonly used mydriatic in paediatric practice. He had no prior history of convulsions. This case demonstrates the uncommon, though serious, atropine-like side effect of cyclopentolate eyedrops (Cyclogyl, Alcon) in usual dosage in a brain damaged child without an epileptic focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 3 publications
0
16
2
Order By: Relevance
“…6,7 For this reason, 0.5% and 1% cyclopentolate usage is suggested. 1,7 However, systemic adverse effects may be seen after 1% cyclopentolate usage such as in our case. It was reported that healthy 23-month-old and 4.5-year-old boys suffer a seizure after 1% cyclopentolate instillation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…6,7 For this reason, 0.5% and 1% cyclopentolate usage is suggested. 1,7 However, systemic adverse effects may be seen after 1% cyclopentolate usage such as in our case. It was reported that healthy 23-month-old and 4.5-year-old boys suffer a seizure after 1% cyclopentolate instillation.…”
Section: Discussionmentioning
confidence: 84%
“…Adverse affects are rare and dose-dependent. 1,2 We report the occurrence of a significant systemic reaction to 1% cyclopentolate eyedrops in a normal dosage manifesting as inability to walk, disequilibrium, dysarthria (incoherent speech), and impaired cognition (disorientation).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Another three-month-old premature boy with mild developmental delay, antidiuretic hormone, and growth hormone deficiency experienced seizures after 0.5% cyclopentolate eye drops [1]. The other three children who experienced seizures were all neurologically impaired, implicating CNS immaturity or possible CNS abnormality as a factor predisposing to the clinical toxicity induced by this drug [8,9]. Also, higher concentrations appeared to result in increasing susceptibility to adverse effects of cyclopentolate in infants, young children, and children with spastic paralysis or other forms of CNS injury.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] This is because both the conjunctival and nasal mucus membranes are good drug-absorbing surfaces, 5,6 and eye drops pass readily through the nasolacrimal duct into the nose. Cases have been reported of seizures 7,8 and other forms of anticholinergic toxicity 9,10 after application of cyclopentolate eye drops.…”
Section: Discussionmentioning
confidence: 99%